Simulation and Validation of the MIDREX Reformer Process using Aspen Plus and Experimental Data - Benrabha, Mohammed Ahmed; Alhaleeb, Mustafa Ahmed; Ben Waly, Abdalhaleem Salim; Eshmila, Seraj Aldeen Omar; Salah, Omnia Mobark (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
The MIDREX reformer process is a technology used for producing synthesis gas from natural gas. The MIDREX reformer process is consider as combination of carbon dioxide and steam reforming process technology for producing syngas This paper presents a simulation of the MIDREX reformer process using Aspen Plus, a process simulation software, and validation of the simulation results with experimental data. The simulation model was developed based on the process flow diagram of the reformer, and the input parameters were temperature, pressure, and steam-to-carbon ratio. The simulation results were validated by comparing them with the data from actual plant. Simulation results had a maximum error of 2.4% for reformed gas temperature and 8% for compositions compared to actual plant data as per validation results. Simulation studied reformer's operating conditions and can optimize MIDREX process for efficiency.
Keywords: Aspen Plus; Experimental data; MIDREX reformer; Simulation; Validation